Diselamatkan Sekali untuk Selamanya? Telaah Kritis terhadap Doktrin Perseverance of The Saints - Denyka Munthe; Jeppri Nainggolan (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2025)
The doctrine of the Perseverance of the Saints-also known as "once saved, always saved"-has been one of the most important tenets of the Reformed tradition. It states that those who are truly chosen and born again will never lose their salvation. However, this doctrine is not free from criticism, both from the perspective of Arminian theology and from the pastoral reality of people who fall into sin. This journal aims to evaluate the biblical basis, systematic logic, and practical implications of this doctrine. The research is conducted through a theological-critical approach, taking into account the primary sources of Scripture and the thought of classical and contemporary theologians. The results show that this doctrine, while having a strong Biblical foundation, requires caution in its application so as not to give rise to a permissive attitude towards sin or neglect the importance of continued growth in faith.